Estudos dos processos erosivos nos cursos hídricos por antropização: o caso da bacia do rio Monjolinho em São Carlos – SP - Apaza, Gabith Sayda Quispe (2024)
Urban rivers are undergoing significant changes in their dynamics, such as straightening, narrowing, widening, and channelization. These transformations are the result of uncontrolled urbanization, which has overlooked the natural characteristics of watercourses and their floodplains, making urbanized areas more susceptible to bank erosion. This study aimed to analyze the effects of urbanization and anthropogenic interventions on marginal erosion processes in the Monjolinho River basin within the urban area of São Carlos, SP, Brazil. The methodology included spatial-temporal analyses of changes in the morphology and alignment of watercourses, anthropogenic interventions, engineering works, and land use and cover. Historical documents and maps from 1970, 1978, 1989, 1998, 2010, and 2023 were utilized, complemented by fieldwork and processed using GIS tools. The study revealed that direct changes to watercourses and modifications in the urban surroundings of the Monjolinho River and Gregório Stream have intensified erosion processes, sedimentation, and sediment deposition in their channels. Soil sample analyses from erosion-prone areas indicated the predominant presence of anthropogenic materials, reflecting improper landfilling and other human interventions that contributed to environmental degradation. The findings demonstrated that the straightening of the Monjolinho River and Gregório Stream, undertaken to meet urban demands, substantially altered their fluvial dynamics over the more than five decades analyzed.